Oligosaccharides Might Contribute to the Antidiabetic Effect of Honey: A Review of the Literature - Mohd S. Ab Wahab (Molecules, 2011)
Evidence shows that honey improves glycemic control in diabetes mellitus. Besides its hypoglycemic effect, studies indicate that honey ameliorates lipid abnormalities in rats and humans with diabetes. The majority of these studies do not examine the mechanisms by which honey ameliorates glycemic and/or lipid derangements. The gut microbiota is now recognized for its ability to increase energy harvest from the diet and alter lipid metabolism of the host. Recently available data implicate a causal role of these gut microbes in the pathophysiology of obesity, insulin resistance, and diabetes mellitus. In this review, we present some of the latest findings linking gut microbiota to pathogenesis of obesity, insulin resistance, and diabetes mellitus. The review also underlines data that demonstrate the beneficial effects of oligosaccharides on various abnormalities commonly associated with these disorders. Based on the similarities of some of these findings with those of honey, together with the evidence that honey contains oligosaccharides, we hypothesize that oligosaccharides present in honey might contribute to the antidiabetic and other health-related beneficial effects of honey. We anticipate that the possibility of oligosaccharides in honey contributing to the antidiabetic and other health-related effects of honey will stimulate a renewed research interest in this field.